2013
DOI: 10.1093/nar/gkt285
|View full text |Cite
|
Sign up to set email alerts
|

The Scaffold attachment factor b1 (Safb1) regulates myogenic differentiation by facilitating the transition of myogenic gene chromatin from a repressed to an activated state

Abstract: The regulation of skeletal muscle gene expression during myogenesis is mediated by lineage-specific transcription factors in combination with numerous cofactors, many of which modify chromatin structure. However, the involvement of scaffolding proteins that organize chromatin and chromatin-associated regulatory proteins has not extensively been explored in myogenic differentiation. Here, we report that Scaffold attachment factor b1 (Safb1), primarily associated with transcriptional repression, functions as a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 66 publications
2
24
0
1
Order By: Relevance
“…Chromatin immunoprecipitation (ChIP) assays using cultured mouse primary myoblasts were performed in triplicate from three independent biological samples as described by Dacwag et al () and Hernandez‐Hernandez et al (). Proliferating cell lysates were incubated overnight with polyclonal rabbit antisera against Brg1 (De la Serna et al, ), or normal rabbit IgG (Santa Cruz Biotechnology, sc‐3888).…”
Section: Methodsmentioning
confidence: 99%
“…Chromatin immunoprecipitation (ChIP) assays using cultured mouse primary myoblasts were performed in triplicate from three independent biological samples as described by Dacwag et al () and Hernandez‐Hernandez et al (). Proliferating cell lysates were incubated overnight with polyclonal rabbit antisera against Brg1 (De la Serna et al, ), or normal rabbit IgG (Santa Cruz Biotechnology, sc‐3888).…”
Section: Methodsmentioning
confidence: 99%
“…For example, SAFB1 functions as a positive regulator of myogenic differentiation, with knockdown of SAFB1 inhibiting the expression of skeletal muscle genes [82]. In this case, interaction with the polycomb PRC2 complex was suggested by the persistence of the Ezh2 component of PRC2 and the repressive histone marker H3K27me3 after SAFB1 knockdown.…”
Section: Transcriptionmentioning
confidence: 99%
“…A study performed on sheep myostatin promoter region showed that the MTBF motif was influential on the transcriptional regulation activity and might play a role in the myostatin gene transcription (Du et al, 2007) alongside with OCT1 (Lakich et al, 1998). The g.66495696T 4C polymorphism changed complementarity of the sequence binding of SATB1 (special AT-rich sequence-binding protein 1) associated with chromatin and the nuclear matrix (De Belle et al, 1998) and also act as co-activator of myogenic genes during myogenic differentiation (Hernández-Hernández et al, 2013). The TATA binding protein factor (VTATA-TBP) together with TATA associated factors (TAF) are components of core promoter T T T C T 0 .…”
Section: Discussionmentioning
confidence: 99%